Characterization of anrmtB‐carrying IncI1 ST136 plasmid in avianEscherichia coliisolates from chickens. Issue 5 (1st May 2016) - Fu, Tong; Du, Xiang‐Dang; Cheng, Pei‐Pei; Li, Xiao‐Ran; Zhao, Xin‐Fang; Pan, Yu‐Shan
Abstract : N/A: The rmtB gene, one of the 16S rRNA methylase genes whose products confer high‐level resistance to aminoglycosides, is most prevalent among Enterobacteriaceae strains. In this study, eight non‐duplicate rmtB ‐carrying avian Escherichia coli strains from a farm in China were isolated and characterized, and further examined by phylogenetic grouping, conjugation experiments and PCR‐based replicon typing. In addition, the genetic environment of rmtB was investigated by cloning and sequencing. Six rmtB ‐carrying E. coli were identified as phylogroup A, sequence type (ST) 156 (A‐ST156), with two assigned to D‐ST117; however, all of them carried the same IncI1 ST136 plasmid. The genetic environment of the rmtB gene in these eight plasmids was the same, as shown by PCR mapping. A multidrug‐resistant region carrying bla TEM‐1, rmtB, a class 1 integron cassette array ( intI1 ‐ dfrA12 ‐ orfF‐aadA2 ‐ qacE Δ 1 ‐ sul1 ) and aacC2 was characterized on the conjugative IncI1 ST136 plasmid. Co‐location of the rmtB gene with a class 1 integron cassette array and aacC2 on the conjugative plasmid will facilitate its maintenance and dissemination.